Carbonate Pore Systems: New Developments and Case Studies 2019
DOI: 10.2110/sepmsp.112.04
|View full text |Cite
|
Sign up to set email alerts
|

Pore Size and Ultrasonic Velocity: Lessons From Miss Lime Reservoirs

Abstract: This article investigates the relationship between rock properties (composition, porosity, and pore architecture) and dry ultrasonic P-wave velocity (VP) of 14 samples representing three facies of the Mid-Continent Mississippian-age Limestone (Miss Lime) units of North–Central Oklahoma. Generally, in carbonate rocks, what drives VP, in addition to bulk porosity (ϕ) and composition, is not straightforward to determine. In this data set, when samples are categorized based on their facies and composition (quartz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Almost all existing studies on V P pressure sensitivity have used rocks with pore-size dominantly in the meso-or larger scale. This paper extends the line of inquiry started by Raj et al (2019) and fills the knowledge gap of examining how nanopores affect dryframe V P pressure sensitivity. Raj et al (2019) demonstrated the effect of pore-size distribution on V P with samples from the Mississippian age mixed carbonate-siliciclastic reservoir rocks from the mid-continent, United States, commonly known as the "Miss Lime" formation.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Almost all existing studies on V P pressure sensitivity have used rocks with pore-size dominantly in the meso-or larger scale. This paper extends the line of inquiry started by Raj et al (2019) and fills the knowledge gap of examining how nanopores affect dryframe V P pressure sensitivity. Raj et al (2019) demonstrated the effect of pore-size distribution on V P with samples from the Mississippian age mixed carbonate-siliciclastic reservoir rocks from the mid-continent, United States, commonly known as the "Miss Lime" formation.…”
Section: Introductionmentioning
confidence: 59%
“…This reduced the number of samples for further analysis to five in Facies A (Figure 5), five in Facies B (Figure 6), and four in Facies C (Figure 7). The second set of plots were along the lines of Figure 3D, which is a crossplots between log 10 A r and log 10 P e of the individual pores, binned to best preserve the continuity of the distribution, e.g., Raj et al (2019). Visualizing data in this manner provided an overview of the pore-size distribution without much regards to the shape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations